All about Your Eyes - Weizer, Jennifer S.; Fekrat, Sharon (Book collections on Project MUSE., 2006)
"A concise, easy-to-understand reference book, All about Your Eyes tells you what you need to know to care for your eyes and what to expect from your eye doctor. In this reliable guide, leading eye care experts: explain how healthy eyes work ; describe various eye diseases, including pink eye, cataract, glaucoma, age-related macular degeneration, and diabetic retinopathy ; provide up-to-date information on eye surgery, including refractive, laser, and cosmetic. For each eye problem, the authors describe in simple, straightforward language."--The publisher - (July 2006)